2020
DOI: 10.3390/ijerph17072246
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practice Behaviour of Midwives Concerning Periodontal Health of Pregnant Patients

Abstract: Maternal gum disease is associated with adverse pregnancy outcomes such as preterm birth and low birthweight. This study aims to evaluate the knowledge, attitudes and practice behaviour of Australian midwives regarding the periodontal health of pregnant women to inform interprofessional antenatal care. This was an observational, cross-sectional study. We circulated an online questionnaire to Australian midwives from August 2018 to February 2019. Key outcome variables were knowledge, attitudes, and practice beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 53 publications
0
20
0
4
Order By: Relevance
“…This could be due to the expert panels in charge of the development of Spanish clinical practice guidelines and clinical protocols intended for the attention to pregnant women by midwives being composed of gynecologists, obstetricians, pediatricians, general practitioners, psychiatrists, nurses, and midwives [ 10 , 50 ]. Thus, as non-dental professionals do not have a deep knowledge of oral healthcare ([ 22 , 24 , 25 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 41 ], and the results of the present study), there is an urgent need for the participation of professionals in the field of odontology in their development.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This could be due to the expert panels in charge of the development of Spanish clinical practice guidelines and clinical protocols intended for the attention to pregnant women by midwives being composed of gynecologists, obstetricians, pediatricians, general practitioners, psychiatrists, nurses, and midwives [ 10 , 50 ]. Thus, as non-dental professionals do not have a deep knowledge of oral healthcare ([ 22 , 24 , 25 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 41 ], and the results of the present study), there is an urgent need for the participation of professionals in the field of odontology in their development.…”
Section: Discussionmentioning
confidence: 90%
“…However, despite more than 80% of the participants indicating that they knew about the relationship between the mother’s and baby’s oral health (Item 13), their knowledge about the association between periodontal disease and adverse pregnancy outcomes was limited (Item 20). In this sense, other studies that were conducted not only with midwives [ 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] but also with other antenatal care providers, such as general practitioners [ 22 , 24 , 31 , 32 ], nurses [ 22 , 25 ], and gynecologists/obstetricians [ 24 , 27 , 30 , 33 ], have highlighted that they have insufficient knowledge about oral health and its influence on systemic health, despite the incorporation of oral health into health-promoting strategies and practices [ 34 ]; moreover, this is highly recommended [ 35 , 36 ]. The high level of specialization required by healthcare professionals together with a population- versus an individual-focused health delivery system have contributed to the separation between oral and general healthcare [ 37 ].…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown that good oral hygiene and gum health are factors that reduce the risk of developing infective endocarditis [21]. Oral infections, especially periodontal disease, increase the level of systemic inflammation and worsen systemic diseases such as diabetes, respiratory disease, cardiovascular disease and osteoporosis [26]. Nguyeni et al, (2020) [26] found that 33% of individuals go to the dentist every 6 months, 33% go to the dentist every 12 months, 21% every 12-18 months, and 12% only go to the dentist if there is pain.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Diperoleh 19,6% responden tidak pernah mengunjungi dokter gigi, 46,1% hanya mengunjungi dokter gigi jika sakit, 30,4% setiap 6 bulan, dan 3,9% setiap 12 bulan. Hasil ini sejalan dengan penelitian Nguyen dkk, 6 yaitu kesadaran mahasiswi kebidanan mengunjungi dokter gigi sekali dalam 6 bulan hanya 33,0%. Menurut Laumara, masyarakat hanya berkunjung bila sudah mengalami sakit gigi.…”
Section: Pembahasanunclassified
“…Penelitian terdahulu oleh Nguyen mendapati 63% mahasiswi kebidanan dan bidan memahami dengan benar bahwa penyakit periodontal adalah kondisi peradangan yang melibatkan infeksi bakteri. 6 Berdasarkan gejala klinis penyakit periodontal, 98 responden (96,1%) sudah menjawab benar dan 4 responden (3,9%) masih menjawab salah. Menurut Nataris, gingivitis adalah bentuk penyakit periodontal dengan gejala klinis gingiva berwarna merah, membengkak dan mudah berdarah tanpa ditemukan kerusakan tulang alveolar.…”
Section: Pembahasanunclassified